2013
DOI: 10.1097/mao.0b013e31826dba43
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Onset Hearing Loss and Vertigo Just Before Posterior Inferior Cerebellar Artery Infarction (Lateral Medulla Syndrome)

Abstract: A 49-year-old woman presented with left-sided sudden hearing loss and tinnitus 1 (Day 1). Audiometric testing revealed a downsloping sensorineural hearing loss and 25% speech discrimination scores at 50 dBHL. She was diagnosed with left idiopathic sudden sensorineural hearing loss (SSNHL) and was managed with intravenous prednisolone administration (beginning at 60 mg/d).On Day 2, she experienced vertigo and, in the emergency department, was found to have a left-beating nystagmus with a torsional component and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…24 However, other lines of evidence suggest a vascular etiology, including mechanisms (increase of prothrombin factors in patients with SHL 25 ) and an epidemiological association with stroke (history of stroke as a risk factor for SHL 26 and increased risk of stroke during 5-year follow-up [HR = 1.64] 11 ). Case reports and case series data suggest SHL can be a prodromal warning sign for a large-vessel disease (AICA infarction, 27 basilar artery occlusion, 28 or, rarely, even posterior inferior cerebellar artery [PICA] infarction 29 ). However, only 3% of AICA infarctions present initially with isolated SHL, compared with 60% with combined audiovestibular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, other lines of evidence suggest a vascular etiology, including mechanisms (increase of prothrombin factors in patients with SHL 25 ) and an epidemiological association with stroke (history of stroke as a risk factor for SHL 26 and increased risk of stroke during 5-year follow-up [HR = 1.64] 11 ). Case reports and case series data suggest SHL can be a prodromal warning sign for a large-vessel disease (AICA infarction, 27 basilar artery occlusion, 28 or, rarely, even posterior inferior cerebellar artery [PICA] infarction 29 ). However, only 3% of AICA infarctions present initially with isolated SHL, compared with 60% with combined audiovestibular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this infarction was mostly associated with the PICA lesion . A case with PICA infarction along with sudden‐onset hearing loss has been previously reported . Although the incidental comorbidity of the sudden sensorineural hearing loss on the side ipsilateral to the LMS cannot be disregarded, we speculate that the ischemia of the inner ear or the vestibulocochlear nerve as one of the most probable causes of the sudden sensorineural hearing loss might be compatible with the large ischemia suspected in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cases presenting with sensorineural hearing loss without cranial nerve deficits in vertebrobasilar artery ischemia are shown in (Table 1) . Sensorineural hearing loss due to AICA syndrome is usually ipsilateral (88%) [6][7][8][9][10][11][12][13][14][15][16][17][18][19], whereas sensorineural hearing loss due to ischemia in the territory of the PICA is also ipsilateral but very rare [20,30]. Although SCA syndrome does not usually lead to hearing loss, contralateral hearing loss has been rarely reported [23,31].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Ischemia of the PICA does not typically result in auditory symptoms because the auditory pathway is not generally involved in the territory of the PICA [59]. However, sensorineural hearing has been reported to occur in the case of infarction in the territory of the PICA (PICA syndrome) in rare cases [20,30,31,60]. Lee found that only 1% of patients reported sudden deafness because of a non-AICA territory vertebrobasilar ischemic stroke [30].…”
Section: Hearing Loss Originating From Infarction Of the Pica Territorymentioning
confidence: 99%